Accidental injection of sodium hypochlorite instead of local anesthetic in a patient scheduled for endodontic procedure - Pushkar Prakash Waknis; Aditya Sunil Deshpande; Samrat Sabhlok (Elsevier, 2011)
ABSTRACT: We present here a case of tissue destruction and paresthesia following the accidental injection of sodium hypochlorite instead of local anesthetic in a patient scheduled for endodontic procedure. The accident was managed by the local injection of steroid, debridement of necrotic tissue, daily dressings and medications. Wound healing was satisfactory at the end of 1 month. An extra-oral scar and a small area of paresthesia persisted even after 5 years.